The Relationship Between Types of Hormon Contraception and Side Effects on Hormonal Contraception Acceptors - winarsih, sri; Chunaeni, Siti; Nikmawati, Nuril (Poltekkes Kemenkes Semarang, 2024)
Background. One of the causes of the delay in the growth rate of development is high population growth. Various ways that are used by the government in increase the growth rate of development is by controlling the population. One of the causes of acceptors who do not continue as acceptors as a result of the side effects experienced must be adequate so that acceptors can understand and reduce anxiety . Hormonal contraception acceptors in the Secang Health Center area also experienced various side effects both related to menstruation and non-menstruation. Research objective: to determine the relationship between the type of use of hormonal contraception and the incidence of side effects on acceptors of hormonal contraception. Methods : this type of research is correlational analytics with a cross-sectional approach. Bivariate test data analysis using the Chie Square test with an error of 5%. Results: There is a relationship between the type of contraception and the side effects of menstrual disorders (amenorrhea and spotting) at p: 0.001; there is a relationship between the type of contraception and the side effects of non-menstrual disorders (nausea, vomiting and dizziness) with p: 0.004. Suggestion: It is necessary to provide information about the kinds of side effects that can occur in hormonal contraception acceptors to prevent anxiety that arises in acceptors so that acceptor dropout does not occur. Keywords: types of hormonal contraception; side effects of menstrual and non-menstrual disorders. 1,2,3 Department of Midwifery, Health Polytechnic of Semarang, Indonesia Jl. Perintis Kemerdekaan Tromol Pos 11, Magelang, Indonesia